THE DILEMMA OF DWINDLING WAGES: A DEEP DIVE INTO CORRUPTION CHALLENGES IN SOKOTO STATE'S CIVIL SERVICE - Abdullahi , Fatima Aisha; Yusuf, Ibrahim Suleiman (International Journal of Political Science and International Relations (IJPSIR), 2024)
Corruption, a pervasive and insidious force, casts a long shadow over political, economic, and social landscapes, impeding progress and eroding the foundations of governance worldwide. This abstract offers a comprehensive examination of the far-reaching impacts of corruption, focusing on its detrimental effects on development efforts, bureaucratic efficacy, and the overall credibility of political institutions. The study contends that corruption, particularly entrenched in the civil service, acts as a formidable barrier to the provision of public goods and services, hindering socio-economic development in afflicted states. Highlighting the interconnectedness of corruption with the abuse of public power for private gain, this abstract elucidates the direct and indirect consequences of corruption on poverty. Drawing from the insights of Chetwynd et al. (2003), the narrative underscores the multifaceted dimensions through which corruption exacerbates the challenges associated with poverty, including low income, deficient health and education services, heightened vulnerability to shocks, and other socio-economic hardships. The study posits that the deleterious effects of corruption are particularly pronounced in countries grappling with issues of economic growth and the complexities of democratic transition. By examining the intricate dynamics between corruption and its cascading impacts on poverty indicators, this research aims to contribute to a nuanced understanding of the complex interplay between corruption and socio-economic development. As nations strive to foster sustainable development and democratic ideals, grappling with the corrosive influence of corruption becomes imperative. This abstract serves as a foundation for further exploration into effective anti-corruption strategies, emphasizing the need for targeted interventions in the civil service to mitigate the detrimental consequences of corruption on public welfare and national progress.